Reduction of Gold (III) and Tellurium (IV) by Enterobacter cloacae MF01 Results in Nanostructure Formation Both in Aerobic and Anaerobic Conditions - Contreras, Fernanda; Vargas, Esteban; Jiménez, Karla; Muñoz-Villagrán, Claudia; Figueroa, Maximiliano; Vásquez, Claudio; Arenas, Felipe (Frontiers in Microbiology, 2018)
Microorganism survival in the presence of toxic substances such as metal(loid)s lies chiefly on their ability to resist (or tolerate) such elements through specific resistance mechanisms. Among them, toxicant reduction has attracted the attention of researchers because metal(loid)-reducing bacteria are being used to recover and/or decontaminate polluted sites. Particularly, our interest is to analyze the toxicity of gold and tellurium compounds for the environmental microorganism Enterobacter cloacae MF01 and also to explore the generation of nanostructures to be used in future biotechnological processes. Resistance of E. cloacae MF01 to gold and tellurium salts as well as the putative mechanisms involved -both in aerobic and anaerobic growth conditions- was evaluated. These metal(loid)s were selected because of their potential application in biotechnology. Resistance to auric tetrachloride acid (HAuCl4) and potassium tellurite (K2TeO3) was assessed by determining areas of growth inhibition, minimum inhibitory concentrations, and growth curves as well as by viability tests. E. cloacae MF01 exhibited higher resistance to HAuCl4 and K2TeO3 under aerobic and anaerobic conditions, respectively. In general, their toxicity is mediated by the generation of reactive oxygen species (ROS) and by a decrease of intracellular reduced thiols (RSH). To assess if resistance implies toxicant reduction, intra- and extracellular toxicant-reducing activities were evaluated. While E. cloacae MF01 exhibited intra- and extracellular HAuCl4-reducing activity, tellurite reduction was observed only intracellularly. Then, Au- and Te-containing nanostructures (AuNS and TeNS, respectively) were synthesized using crude extracts from E. cloacae MF01 and their size, morphology and chemical composition was evaluated.